2008
DOI: 10.1111/j.1601-5037.2008.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported oral health perceptions of Somali adults in Minnesota: a pilot study

Abstract: A substantial proportion of Somali adults rated their oral health and access to dental care as poor/fair. These findings suggest that this population would benefit from improved access to oral health care and culturally appropriate oral health education and promotion programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
3
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 9 publications
5
18
3
7
Order By: Relevance
“…The majority of NYC adults 71.1% reported a primary care visit, and 60.4% reported a dental care visit. These findings are similar to the national oral health utilization patterns with 60.6% of Americans reporting an oral healthcare visit in 2013 . While the overall PCV utilization was greater than DCV during this 1‐year period, approximately 806 000 adults (12.9%) had a dental visit but no medical visit.…”
Section: Discussionsupporting
confidence: 77%
“…The majority of NYC adults 71.1% reported a primary care visit, and 60.4% reported a dental care visit. These findings are similar to the national oral health utilization patterns with 60.6% of Americans reporting an oral healthcare visit in 2013 . While the overall PCV utilization was greater than DCV during this 1‐year period, approximately 806 000 adults (12.9%) had a dental visit but no medical visit.…”
Section: Discussionsupporting
confidence: 77%
“…We found that adults who were married were more likely to report good SROH. Similar finding has been reported in a recent study conducted in Somali adults (Okunseri et al, 2008a). Associations between SROH and socio-economic position markers (e.g., education, occupation, household income, household wealth, subjective social status and childhood socio-economic position) have been reported in several studies (Borrell&Baquero, 2011;Finlayson et al, 2010;Locker, 2009;Pattussi et al, 2010;Wu et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…A set of independent individual-level variables were identified that may influence SROH: (1) exogenous variables (age, gender); (2) personal characteristics of primary determinants of oral health (predisposing socio-demographic and health beliefs factors -education, marital status, oral health locus of control (LOC) beliefs, perceived general health status; enabling characteristics -socio-economic status, having dental insurance; need factors -perceived dental treatment need, self-reported number of teeth, self-reported dental pain and dental problems, and (3) oral health behaviors (frequency of tooth brushing, dental attendance pattern, use of dental floss). A number of studies showed that demographic and socio-economic variables such as gender, age, income and marital status have been associated with SROH (Borrell & Baquero, 2011;Finlayson et al, 2010;Kim et al, 2010;Okunseri et al, 2008a;Patussi et al, 2010;Ugarte et al, 2007;Wu et al, 2011). Previous studies showed that individuals who perceive better oral health had a higher frequency of seeking preventive dental care (Araújo et al, 2009;Camargo et al, 2009;Gilbert et al, 2003;Matos&Lima-Costa, 2006;Okunseri et al, 2008b;Pavi et al, 2010;Thomson et al, 2010;Woolfolk et al 1999;Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The use of dental services would be more likely explained by social structure, belief and enabling factors than need factors [13]. Additionally, though this study only considered the pattern of dental attendance and not the last visit our findings were consistent with the literature in that a significant proportion had never attended a dentist [28]. Furthermore, amongst this study sample social participation has been found to be protective from ‘symptomatic’ dental attendance.…”
Section: Discussionsupporting
confidence: 81%